2017
DOI: 10.1248/cpb.c16-00868
|View full text |Cite
|
Sign up to set email alerts
|

Aglaiabbrevins A–D, New Prenylated Bibenzyls from the Leaves of <i>Aglaia abbreviata</i> with Potent PTP1B Inhibitory Activity

Abstract: Four new prenylated bibenzyls, named aglaiabbrevins A-D (2, 4-6), were isolated from the leaves of Aglaia abbreviata, along with two known related analogues, 3,5-dihydroxy-2-[3,7-dimethyl-2(E),6-octadienyl] bibenzyl (7) and 3,5-dihydroxy-2-(3-methyl-2-butenyl)bibenzyl (8). The structures of the new compounds were elucidated on the basis of extensive spectroscopic experiments, mainly one and two dimensional (1D-and 2D)-NMR, and the absolute configuration of 5 was determined by the measurement of specific rotati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The recombinant PTP1B catalytic domain was expressed and purified according to the methodology as previously reported. The enzymatic activities of the PTP1B catalytic domain were determined at 30 °C by monitoring the hydrolysis of p NPP. Dephosphorylation of p NPP generated the product p NP, which was monitored at an absorbance of 405 nm with an EnVision multilabel plate reader (Perkin–Elmer Life Sciences, Boston, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The recombinant PTP1B catalytic domain was expressed and purified according to the methodology as previously reported. The enzymatic activities of the PTP1B catalytic domain were determined at 30 °C by monitoring the hydrolysis of p NPP. Dephosphorylation of p NPP generated the product p NP, which was monitored at an absorbance of 405 nm with an EnVision multilabel plate reader (Perkin–Elmer Life Sciences, Boston, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Leading to apoptosis [34].Antidiabetic activitySun et al confirmed prenylated bibenzyls named aglaiabbrevins A-D isolated from the leaves of Aglaia abbriviata inhibits protein tyrosine phosphatase-1B (PTP1B). These prenylated bibenzyls may be considered as lead compounds for the development of new antiobesity and antidiabetic agents[35].Anti-inflammatory activityLiu et al derived anti-inflammatory activity and other antioxidant, antimicrobial activities from the medicinal plants honey, made from different floral sources. Floral honey from Aglaia formosana was involved in testing of anti-inflammatory activity [36]…”
mentioning
confidence: 99%